PENENTUAN PERSAMAAN BARU UNTUK MENENTUKAN ULTIMATE RECOVERY FACTOR PADA RESERVOIR MINYAK DI BAWAH KONDISI WATERFLOODING PADA LAPANGAN X - Aria Widjaya, Jody
Study in the field X which is an oil reservoir focused on parameters sensitivity that influence determination of the ultimate recovery factor (URF), it’s important to estimate the recoverable reserves or remaining reserves as a first step of development of a field. This study uses field data to create a model of reservoir and further develop sensitivity analysis geological, reservoir and waterflooding parameters. X field is a field that located in the South Sumatera Basin. By using reservoir simulation, reservoir performance prediction is done when using waterflooding to increase recovery factor. Black oil simulator used to predict recovery of hydrocarbons in a variety of reservoir conditions. Design of Experiment (DOE) fractional factorial model is used to find a new equation to determine URF on Field X. The aim of this study was to develop a new equation which is more accurate for estimating the value of recovery factor of a field based on general form of Guthrie and Greenberger equation which is considering several parameters such as permeability, porosity, initial water saturation, reservoir thickness and oil viscosity with taking into account the magnitude of water rate injected into the reservoir and time when it does waterflooding. These parameters are simulated in the simulator black oil with certain minimum and maximum values to see the effect it has on the ultimate recovery factor. Model Design of Experiment (DOE) fractional factorial model generated to determine URF in the field X showed excellent results against the simulation results with a difference of only 3.2% and R2 value of 0.8589. This shows that the regression equation is valid for use in the estimation of URF in Field X. According to the study it can be concluded that for the parameters: injection time and porosity do not have a significant effect, while the parameters: permeability, oil viscosity, initial water saturation and reservoir thickness significantly affect the value of URF. The result of equation is capable to represent regression model in calculation URF in Field X within the limits of certain value.